Temporal Relationship Between Treatment Burden and Self-Care and Its Impact on Systolic Blood Pressure and Hypertension Control - Jia Z; Niu Z; Xie YJ; Su Z; Wang JJ; Hernandez J; Li YT; Wang HHX (International Journal of General Medicine, 2025)
Zhihui Jia,1 Zimin Niu,1 Yao Jie Xie,2 Zhiran Su,3 Jia Ji Wang,4 Jose Hernandez,5,6 Yu Ting Li,7 Harry HX Wang1 1School of Public Health, Sun Yat-Sen University, Guangzhou, People’s Republic of China; 2School of Nursing, The Hong Kong Polytechnic University, Hung Hom, Hong Kong SAR; 3Faculty of Education, Monash University, Melbourne, Australia; 4School of Public Health, Guangzhou Medical University, Guangzhou, People’s Republic of China; 5Green Templeton College, University of Oxford, Oxford, UK; 6Department of Precision Health, Luxembourg Institute of Health, Luxembourg, Luxembourg; 7Zhongshan Ophthalmic Center, Sun Yat-Sen University, Guangzhou, People’s Republic of ChinaCorrespondence: Yu Ting Li, Zhongshan Ophthalmic Center, Sun Yat-Sen University, Guangzhou, 510060, People’s Republic of China, Email liyuting3@mail.sysu.edu.cn Harry HX Wang, School of Public Health, Sun Yat-Sen University, Guangzhou, 510080, People’s Republic of China, Email haoxiangwang@163.com; wanghx27@mail.sysu.edu.cnBackground: Effective blood pressure (BP) control necessitates sustained adherence to self-care regimes; however, adherence can be undermined by excessive treatment burden. The longitudinal dynamics between treatment burden and self-care behaviours remain less understood, with particularly limited understanding of how the temporal relationship may influence BP control.Objective: This study sought to examine the temporal relationship between treatment burden and self-care while investigating their collective longitudinal impact on both systolic BP levels and hypertension control.Methods: We investigated a community-based longitudinal cohort of 1718 hypertensive patients (mean age 54.6 ± 11.9 years; 28.5% with coexisting diabetes). Treatment burden and self-care were measured at two time points (T1 and T2), separated by an approximate 11-month period, with BP measured in the subsequent 14 months (T3). We employed cross-lagged panel modelling and mediation analysis to examine the temporal relationship between treatment burden and self-care (from T1 to T2) and their collective influence on systolic BP and hypertension control (T3).Results: After adjusting for covariates, we observed a significant cross-lagged path coefficient between treatment burden (T1) and self-care (T2) in the total sample (path coefficient = − 0.089, P< 0.001). The association remained consistent across subgroups–including individuals aged less than 60 years (path coefficient = − 0.083), aged 60 years and above (path coefficient = − 0.113), diabetic patients (path coefficient = − 0.103), and non-diabetic patients (path coefficient = − 0.085), with all P< 0.001. The mediation analyses demonstrated that self-care (T2) accounted for 10.7% (P< 0.001) and 11.1% (P< 0.001) of the total effect of treatment burden (T1) on systolic BP and hypertension control (T3), respectively.Conclusion: Our study findings establish a temporal sequence wherein elevated treatment burden precedes suboptimal self-care capacity, which in turn adversely affects subsequent BP control. The nature of such association opens the door for further primary care research on developing more sustainable hypertension management strategies.Keywords: treatment burden, self-care, systolic blood pressure, hypertension control, cross-lagged panel model, mediation analysis